Issues & Options of Sustainable Livelihoods and Biodiversity Conservation of High Altitude Community Forests of Pyuthan District - Thaker, RB; KC, Nahakul; Subedi, Ramu; Brahmmney, Peter; Yadav, NP; Phulara, Nirmala Kr (The Initiation, 2010)
Community Forest is one of the most successful forestry programs; however, it has several anomalies pertaining to the high altitude community forests. Construction of Goth (small hut) , cultivation of crops , wildlife hunting , heavy grazing and lopping and haphazard NTFP collection are the major issues of high altitude community forests whereas it possesses a large range of pasture land which provides livestock for grazing as well as valuable NTFPs for collectors. It is also a reservoir of important and commercially viable biological diversity which has a great potential for bio-prospecting. Key Words: Livelihoods, NTFPs, Wildlife conflict, Land tenure, Pasture land, Epidemic disease, Wetlands, Bio-prospecting, Indigenous knowledge & Skill technology (IKST) DOI: 10.3126/init.v2i1.2544 The Initiation Vol.2(1) 2008 pp202-211